2006
DOI: 10.1103/physrevc.73.024307
|View full text |Cite
|
Sign up to set email alerts
|

First investigation of excited states in the odd-proton nucleusFr209

Abstract: Excited states in 209 Fr were produced following the 176 Yb( 37 Cl, 4n) reaction. An excitation function was measured with data taken at 173, 179, and 185 MeV. Recoiling fusion-evaporation products were separated using the SASSYER gas-filled spectrometer. HPGe clover detectors of the YRAST Ball array at the target position and at the focal plane were used to detect prompt and delayed gamma ray decays, providing the first spectroscopic information about prompt and delayed transitions in 209 Fr. The decay from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 32 publications
1
8
1
Order By: Relevance
“…The 203, 257, 520, 701, 721, and 817 keV lines were also observed in the γ -γ -coincidence studies of our earlier work with 12 Although the present γ -γ -time coincidence results confirm the arrangement of transitions and levels claimed in Ref. [4] with an isomeric state decaying through a 194 and 632 keV cascade, from our excitation function results and cross bombardments, we assign it to 208 Fr, rather than to 209 Fr. (A report on 208 Fr has been published [5], and 210 Fr will be the subject of a later study.)…”
Section: A Reaction Conditions and Isotopic Assignmentssupporting
confidence: 87%
See 4 more Smart Citations
“…The 203, 257, 520, 701, 721, and 817 keV lines were also observed in the γ -γ -coincidence studies of our earlier work with 12 Although the present γ -γ -time coincidence results confirm the arrangement of transitions and levels claimed in Ref. [4] with an isomeric state decaying through a 194 and 632 keV cascade, from our excitation function results and cross bombardments, we assign it to 208 Fr, rather than to 209 Fr. (A report on 208 Fr has been published [5], and 210 Fr will be the subject of a later study.)…”
Section: A Reaction Conditions and Isotopic Assignmentssupporting
confidence: 87%
“…For still lighter isotopes, the valence neutron holes are expected to play a more important role. In 210 Fr(N = 123), a number of excited states have been assigned from the α decay of 214 Ac [3], but these are necessarily of relatively low spin, while a recent high-spin study by the Yale group reported a set of transitions for 210 Fr and a partial level scheme for 209 Fr [4]. However, our study does not agree with the latter assignments.…”
Section: Introductioncontrasting
confidence: 90%
See 3 more Smart Citations